Relationship of Nutritional Status, Role of Swallowing Drug Supervisors and Family Support with the Successful Treatment of Lung Tuberculosis in Southwest Sumba Distric - Kono, Maria Roswita Milla; Purnawan, Sigit; Ndun, Helga J. N (Faculty of Public Health, Nusa Cendana University, 2021)
Tuberculosis (TB) is one of the infectious diseases caused by the bacterium Mycobacterium tuberculosis and is still a public health problem related to environmental conditions and community behavior. The success of treatment and case detection are indicators used to measure the effectiveness of TB control.Pulmonary TB disease can be cured with regular treatment. The success of treatment is influenced by several factors ranging from patient characteristics including nutritional and immune status, environmental factors, facilities and infrastructure factors that support regularity of treatment.The cure to be achieved requires regular treatment for each patient. Compliance in taking medication is very important to avoid drug resistance, so direct supervision by the PMO is needed and also support from the family.The purpose of the study was to determine the relationship between nutritional status, the role of PMO and family support with the success of pulmonary TB treatment. This research design uses a case control method with a retrospective approach. The results of the analysis showed that nutritional status (ρ= 0.002), the role of PMO (ρ= 0.001), family support (ρ= 0.001) had a significant relationship with the success of pulmonary TB treatment. It was concluded that nutritional status, the role of PMO, family support were very influential on the success of pulmonary TB treatment this was related to the body's immune system and also helped pulmonary TB patients in carrying out treatment to completion and recovering to avoid transmission and drug resistance.